2010
DOI: 10.1002/adsc.201000564
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Propiolic Acids via Copper‐Catalyzed Insertion of Carbon Dioxide into the CH Bond of Terminal Alkynes

Abstract: A highly effective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(74 citation statements)
references
References 44 publications
3
70
0
1
Order By: Relevance
“…[5] Most recently, the catalytic carboxylation of CÀ H-acidic molecules was described for heterocycles, [6] polyhalogenated arenes, [6] and terminal alkynes. [7] The synthesis of acrylic acid from ethene and CO 2 in a stepwise manner was described; [8] this approach enabled repeated use of the Ni reagent corresponding to approximately 10 turnovers. [9] Furthermore, some examples were reported in which coupling reactions between CO 2 and alkenes, [10] dienes, [11] allenes, [12] or alkynes [13] in the presence of Pd, Ni, or Fe catalysts and superstoichiometric amounts of organometallic reducing agents, such as ZnR 2 , AlR 3 , Grignard reagents, and silanes, gave carboxylic acids after aqueous work up.…”
mentioning
confidence: 99%
“…[5] Most recently, the catalytic carboxylation of CÀ H-acidic molecules was described for heterocycles, [6] polyhalogenated arenes, [6] and terminal alkynes. [7] The synthesis of acrylic acid from ethene and CO 2 in a stepwise manner was described; [8] this approach enabled repeated use of the Ni reagent corresponding to approximately 10 turnovers. [9] Furthermore, some examples were reported in which coupling reactions between CO 2 and alkenes, [10] dienes, [11] allenes, [12] or alkynes [13] in the presence of Pd, Ni, or Fe catalysts and superstoichiometric amounts of organometallic reducing agents, such as ZnR 2 , AlR 3 , Grignard reagents, and silanes, gave carboxylic acids after aqueous work up.…”
mentioning
confidence: 99%
“…To a stirred solution of 3-(2-methoxyphenyl) prop-2-ynoic acid [15] (0.706 g, 4.00 mmol) and 4-methylmorpholine (0.607 g, 6.00 mmol) in tetrahydrofuran (THF, 20 mL) was added isobutyl chloroformate (0.656 g, 4.80 mmol) in THF (3 mL) at 0°C, and the mixture was stirred at 0°C for 0.5 h. 1-Naphth-Scheme 4. Possible mechanism for the formation of 4a and 5a from 3a.…”
Section: N-[(furan-3-yl)methyl]-3-(2-methoxyphenyl)-n-(naphthalen-1-ymentioning
confidence: 99%
“…[20] Propiolic acids extrude CO 2 at low temperatures, [21] which has recently been shown to be reversible. [22] In contrast to most other decarboxylative couplings, decarboxylative Sonogashira reactions can thus be performed at remarkably low temperatures. Lee and coworkers have demonstrated that various propiolic acids can be coupled with aryl bromides and iodides at 80°C using a monometallic palladium catalyst.…”
Section: Introductionmentioning
confidence: 99%